Keanekaragaman Jenis Tumbuhan dan Status Konservasi Tumbuhan di Kebun Raya Katingan : Plant Species Diversity and Conservation Status in Katingan Botanical Garden - Setiarno, Setiarno; Sari , Nurmila; Sosilawaty, Sosilawaty; Hidayat, Nisfiatul; Junaedi, Ajun (HUTAN TROPIKA, 2023)
The existence of the Katingan Botanical Garden which will collect various plants (fruits, orchids, and various types of forest vegetation typical of Kalimantan) will be utilized and developed for research, education, cultivation, conservation, tourism, and environmental services. This study aims to analyze the diversity and reveal the rarity status of plant species in the Katingan Botanical Garden area, Katingan Regency, Central Kalimantan Province. The method used to collect vegetation data is the plot method in the form of quadratic transects. The size of the observation plot transect is 20 m x 500 m with 2 (two) transects. The research object is seedling, sapling, pole, and tree-stage vegetation. The composition of vegetation species found in the community unit (2,0 ha) is 28 species belonging to 17 tribes, in this, there are 2 individuals that have not been identified. Akasia (Acacia mangium), Tumih (Cambretocarpus rotundatus), and Gerunggang (Cratoxylum arborescent BI.) dominated at all growth stages. The biodiversity indices (diversity, richness, and evenness indices) are classified as medium, low, and high, respectively. There are 3 (three) plant species classified as IUCN status, namely Pulai (Alstonia scholaris) with Least Concern (LC) or low-risk criteria, Jelutung (Dyera lowii) with Vulnerable (VU) or vulnerable criteria, Kempas (Koompassia malaccensis) with Vulnerable (VU) or vulnerable criteria, and 1 (one) plant species including protected, namely Kempas (Koompassia malaccensis).